Pengujian User Experience Aplikasi Perangkat Bergerak Jagoan Indonesia Menggunakan Metode Usability Testing - Erlangga Rizki Pratama; Eriq Muhammad Adams Jonemaro; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Modernization requires all areas of human life to be fast and easy, including education. As is the case with activities to increase a sense of nationalism through learning Indonesian culture, carried out with methods that are creative, innovative, fun and not boring (Fadillah, 2016). Learning can use the application "Jagoan Indonesia" on mobile devices. In this game, there are main functions, namely exploring, puzzles and quizzes. Puzzles are used to match the map of Indonesia with regional names, however the roaming and quiz functions are still under development. In order to adapt to the current state of the user, it is necessary to measure the quality and design to make it more user friendly in terms of users and to make a good user experience must be good usability. In this study using usability testing. Usability testing is used on of learnability, efficiency , errors and level of satisfaction (Nielson, 2012). In this case, the sample of test was taken from 10 students of MI Plandi 1. Performed in two scenarios, namely without the application and with the application. The purpose of this study was to find out the process and results of usability testing on the mobile application "Jagoan Indonesia" in class students. 4-6 MI Plandi 1. The results of the calculation using usability tasting are in the form of Learnability 100%, Efficiency 0.0027, Error 0.2 and Satisfaction 69,00 and acceptance on high categori. Thus, it can be said that the application on Indonesian whiz mobile devices can be accepted and used well by respondents. It is also influenced by the age factor of the respondents who mostly enter adolescence and most of them are female, which is able to increase the acceptance of new material well.